Predictors for success in students enrolled in an accelerated, second degree, Bachelor of Science in Nursing program. - Kay CS (Predictors for Success in Students Enrolled in an Accelerated, Second Degree, Bachelor of Science in Nursing Program, 2009)
Six years of data from an accelerated Bachelor of Science in Nursing (BSN) program student records, from a large state university, explored the relationship between certain academic and demographic predictors available prior to admission, and the performance outcomes of continuation or discontinuation of the accelerated BSN program. Data analyzed included student age, gender, ethnicity and language, type of first bachelor's degree, tier of undergraduate university, undergraduate grade point average, mathematics taken during the primary bachelor's degree and courses required as admission prerequisites. Descriptive statistics, univariate and multivariate analyses were used to determine which factors predicted success in this accelerated BSN program. This research may be useful for admission decisions, in light of limited cohort placement in accelerated BSN programs and the looming nursing shortage. Benner's Nursing Theory of Novice to Expert (2001) was utilized to highlight the importance of a firm grasp of foundational nursing knowledge prior to moving forward to more difficult nursing concepts as encountered in the second semester of an accelerated BSN program. The following study null hypotheses were confirmed for the variables of tier, UGPA, prerequisite GPA, prerequisite course grades in anatomy, physiology, chemistry, microbiology, and undergraduate mathematics for all the dependent variable program outcomes. The hypothesis that examined which demographics factors are associated with the accelerated BSN program outcomes found, in the bivariate analyses, a significant difference by gender, age and English language skills and graduation from the accelerated BSN program. Female gender (OR = 3.047, 95% CI 1.107--8.385), younger age (<= 30) (OR = .919, 95% CI 0.865--0.977) and English as the primary language (OR = 4.040, 95% CI 1.070--15.261) were demonstrated to be significant predictors of first semester outcomes, however ethnicity did not. The final logistic regression for graduation from the accelerated BSN program demonstrated only age (<= 30) to be a predictor of success. In the final logistic regression for completion of either the accelerated or traditional BSN program, only English as the primary language was predictive of success. This dissertation emphasizes that solutions to the problem of at risk student failure must be considered prior to acceptance into an accelerated BSN program. Such students may be encouraged to pursue the traditional BSN or associate degree options, from the inception of their nursing education, or have pre-acceptance remediation. It is important to note that these options are superior to experiencing the disappointment of a failed start in the accelerated BSN program and a possible loss to the nursing profession altogether.